Legal Certainty of Indigenous Peoples' Customary Land Rights in Relation to Cultivation Rights : A Legal Certainty Perspective in West Kutai - Tarisa; Imam Koeswahyono; Supriyadi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2027)
This study examines the nature of land disputes between the Intu Lingau Indigenous Community and holders of plantation cultivation rights in West Kutai Regency and proposes a dispute resolution model based on the principle of legal certainty. It employs normative legal research using statutory, conceptual, and case approaches, analyzed through the theory of legal certainty. The research gap lies in the absence of studies specifically addressing the normative conflict between the recognition of indigenous communal land rights and the cultivation rights regime as the primary source of legal uncertainty in land dispute resolution. The findings reveal that the dispute extends beyond land control, reflecting a normative conflict between the constitutional recognition of hak ulayat and the state's grant of cultivation rights without an integrated legal framework. Consequently, dispute resolution mechanisms through regional governments and agrarian authorities have not provided definitive legal certainty. The novelty of this study is a legal certainty-based dispute resolution model consisting of three stages: recognition of indigenous communities and their customary territories, verification and legal audit of cultivation rights, and deliberation based on the audit results as the basis for settlement. This model is expected to strengthen legal certainty, protect indigenous communal land rights, and promote a more coherent land law system in Indonesia.